2018
DOI: 10.1007/s11892-018-1105-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Health Information Technologies on Glycemic Control Among Patients with Type 2 Diabetes

Abstract: Purpose of ReviewThis study was to present meta-analysis findings across selected clinical trials for the effect of health information technologies (HITs) on glycemic control among patients with type 2 diabetes.Recent FindingsHITs may be promising in diabetes management. However, findings on effect size of glycated hemoglobin level (HbA1c) yielded from HITs varied across previous studies. This is likely due to heterogeneity in sample size, adherence to standard quantitative method, and/or searching criteria (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 77 publications
2
22
0
Order By: Relevance
“…usual care [33]. This result suggests that HITs are the key to the effectiveness rather than tools or components of these trials.…”
Section: Hits In Glycemic Control Among Patients With T2dmentioning
confidence: 96%
See 3 more Smart Citations
“…usual care [33]. This result suggests that HITs are the key to the effectiveness rather than tools or components of these trials.…”
Section: Hits In Glycemic Control Among Patients With T2dmentioning
confidence: 96%
“…However, these studies often included limited number of trials [21], lack of adherence to standard quantitative methods [25], inadequate attention to heterogeneity across studies [26], lumped nonrandomized and randomized trials together into evaluation [19,23,25,[27][28][29], mixed participants with type 1 or type 2 diabetes into analysis [18,22,25,[27][28][29], or restricted searching criteria to a particular patient population or a specific type of HIT [27,[30][31][32]. To address these limitations and to verify if and how much HITs impact glycemic control, Yoshida and colleagues recently conducted a meta-analysis to examine the most current state of evidence from RCTs concerning the effect of HITs on HbA1c reduction among patients with T2D [33]. From an analysis of 34 eligible studies (40 estimates) identified from multiple databases from January 1946 to December 2017, the study reported that introduction of HITs to standard diabetes treatment resulted in a statistically reduced HbA1c.…”
Section: Hits In Glycemic Control Among Patients With T2dmentioning
confidence: 99%
See 2 more Smart Citations
“…However, policies and regulations are necessary for privacy and security issues [28]. A study using health information technologies on glycemic control with type 2 diabetes was considered in [29] reporting better control both clinically and statistically. A reduction of HbA1c was observed in all the interventions presented.…”
Section: Related Workmentioning
confidence: 99%